2017
DOI: 10.1094/mpmi-11-16-0236-r
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Functions Are Required for Growth and Development of Magnaporthe oryzae

Abstract: RNA interference (RNAi) is conserved in eukaryotic organisms, and it has been well studied in many animal and plant species and some fungal species, yet it is not well studied in fungal plant pathogens. In the rice blast fungus Magnaporthe oryzae, we examined small RNA (sRNA) and their biogenesis in the context of growth and pathogenicity. Through genetic and genomic analyses, we demonstrate that loss of a single gene encoding Dicer, RNA-dependent RNA polymerase, or Argonaute reduces sRNA levels. These three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 70 publications
2
41
0
Order By: Relevance
“…DCLs are the most important components of the RNAi machinery in eukaryotes, and in the present study, downregulation of the DCL2-like gene was revealed, but the DCL1-like gene in P. italicum did not significantly reduce in its ability to infect citrus fruits (Figures 2 and 3). Subsequent sRNA sequencing also indicated that the DCL2-like gene plays a more important role in regulating milRNA expression than the DCL1-like gene in P. italicum ( Figure 6), as similarly reported in Magnaporthe oryzae [45]. These data suggest that P. italicum may possess a mechanism of RNAi or ck-RNAi and that its sRNA might be an effector in citrus epidermal cells that induces the RNAi response of citrus fruits during the infection process.…”
Section: Discussionsupporting
confidence: 74%
“…DCLs are the most important components of the RNAi machinery in eukaryotes, and in the present study, downregulation of the DCL2-like gene was revealed, but the DCL1-like gene in P. italicum did not significantly reduce in its ability to infect citrus fruits (Figures 2 and 3). Subsequent sRNA sequencing also indicated that the DCL2-like gene plays a more important role in regulating milRNA expression than the DCL1-like gene in P. italicum ( Figure 6), as similarly reported in Magnaporthe oryzae [45]. These data suggest that P. italicum may possess a mechanism of RNAi or ck-RNAi and that its sRNA might be an effector in citrus epidermal cells that induces the RNAi response of citrus fruits during the infection process.…”
Section: Discussionsupporting
confidence: 74%
“…The number of AGO-like genes varied from 1 ( A. nidulans, S. pombe ) to 4 ( Cryphonectria parasitica, Gaeumannomyces graminis ) but most of the fungal species examined here possessed three AGO-like genes. Based on their amino acid sequences in the Piwi domain, the AGO genes were clustered into three major groups, which corresponded to the AGO1, AGO2 and AGO3 groups reported previously (62). Three AGO genes in P. oryzae were designated MoAGO1 (MGG 14873), MoAGO2 (MGG 13617) and MoAGO3 (MGG 01294) (62).…”
Section: Resultsmentioning
confidence: 89%
“…Based on their amino acid sequences in the Piwi domain, the AGO genes were clustered into three major groups, which corresponded to the AGO1, AGO2 and AGO3 groups reported previously (62). Three AGO genes in P. oryzae were designated MoAGO1 (MGG 14873), MoAGO2 (MGG 13617) and MoAGO3 (MGG 01294) (62). Protein domain analysis using InterPro Scan revealed that all three proteins possessed conserved domains (N-terminal, linker 1, PAZ, linker 2 and Piwi) and conserved amino acid residues (nucleic acid binding site, 5′ RNA guide strand anchoring site and enzymatic active site) (Figure 1B).…”
Section: Resultsmentioning
confidence: 89%
“…A priority now is to determine how widely the deployment of sRNA effectors is conserved among plant‐associated fungi with contrasting lifestyles, including endophytes and symbionts. For example, the P. oryzae and F. graminearum ΔΔdcl1:dcl2 Dicer‐like double mutants are still pathogenic, suggesting that these fungal species do not use DICER‐dependent sRNA to manipulate host plant defences, as observed with B. cinerea (Raman et al ., ; Zeng et al ., ).The discovery of sRNA effectors raises many other questions: to what extent is the expression of fungal sRNA effectors constitutive or plant‐induced; are specific sRNA populations produced at different infection stages to target different sets of host genes; and do wide host‐range pathogens produce different populations of sRNA effectors when infecting different hosts?…”
Section: Small Rnas New Fungal Effectors Targeting Plant Gene Expresmentioning
confidence: 99%